2015
DOI: 10.1016/j.saa.2014.07.060
|View full text |Cite
|
Sign up to set email alerts
|

Complex formation of Sn(II) with glycine: An IR, DTA/TGA and DFT investigation

Abstract: The novel Sn(Gly)2⋅H2O complex compound has been synthesized and characterized by TGA, IR and Raman spectroscopy. Molecular spectroscopy and ab initio simulation have given the evidence of glycine molecule being coordinated to Sn(II) as bidentate chelating ligand by oxygen atom of carboxyl group and nitrogen atom of amino group. Water molecule is bonded with amino and carboxylic groups by hydrogen bonds in the out sphere. The M06, TPSS, TPSSm, TPSSh and revTPSS density functionals have been tested for calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…[ 44 ] The coordination between Zn 2+ and COO − was confirmed via FT‐IR measurement, in which an upward shift was observed for the characteristic band for COO − , Figure 3c. [ 41 ] 1 H nuclear magnetic resonance (NMR) on different solutions confirmed that the H originated from the –CH 2 – of the glycine with a characteristic peak located at ≈3.4 ppm, that shifts to ≈3.27 and ≈3.12 ppm for, respectively, 1 M ZnSO 4 –3 M glycine and 1 M ZnSO 4 –1 M glycine (Figure S6, Supporting Information). The negative shift evidence decreased electron density because of an inductive effect caused by the interaction between Zn 2+ and carboxy/amino group.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…[ 44 ] The coordination between Zn 2+ and COO − was confirmed via FT‐IR measurement, in which an upward shift was observed for the characteristic band for COO − , Figure 3c. [ 41 ] 1 H nuclear magnetic resonance (NMR) on different solutions confirmed that the H originated from the –CH 2 – of the glycine with a characteristic peak located at ≈3.4 ppm, that shifts to ≈3.27 and ≈3.12 ppm for, respectively, 1 M ZnSO 4 –3 M glycine and 1 M ZnSO 4 –1 M glycine (Figure S6, Supporting Information). The negative shift evidence decreased electron density because of an inductive effect caused by the interaction between Zn 2+ and carboxy/amino group.…”
Section: Resultsmentioning
confidence: 90%
“…This glycine additive possesses one carboxy and one amino, group, and reportedly has a stronger coordination ability with the metal ions than with the water molecules. [ 41,42 ] Characterization techniques, including, Raman, FT‐IR, and NMR were used to determine solvation structure evolution in the ZnSO 4 ‐glycine electrolyte. The Raman spectra, Figure a, show that the characteristic C‐N stretching vibration band located at 1035 cm −1 in pure glycine solution shifts to a higher wavenumber on the addition of ZnSO 4 salt to the electrolyte, evidencing strong interaction between Zn 2+ and N atoms in the additive.…”
Section: Resultsmentioning
confidence: 99%
“…Novikova et al[17] synthesized tin-glycine complex [Sn(Gly)2•H 2 O] and characterized by TGA, IR and Raman spectroscopy. It was found that glycine molecule is coordinated to Sn(II) as bidentate chelating ligand by oxygen atom from the carboxyl group and nitrogen atom of a glycine molecule (Figure 2.7).…”
mentioning
confidence: 99%